Air pollution, ethnicity and telomere length in east London schoolchildren: An observational study. (November 2016) - Walton, Robert T.; Mudway, Ian S.; Dundas, Isobel; Marlin, Nadine; Koh, Lee C.; Aitlhadj, Layla; Vulliamy, Tom; Jamaludin, Jeenath B.; Wood, Helen E.; Barratt, Ben M.; Beevers, Sean; Dajnak, David; et al.
Abstract: Background: Short telomeres are associated with chronic disease and early mortality. Recent studies in adults suggest an association between telomere length and exposure to particulate matter, and that ethnicity may modify the relationship. However associations in children are unknown. Objectives: We examined associations between air pollution and telomere length in an ethnically diverse group of children exposed to high levels of traffic derived pollutants, particularly diesel exhaust, and to environmental tobacco smoke. Methods: Oral DNA from 333 children (8–9 years) participating in a study on air quality and respiratory health in 23 inner city London schools was analysed for relative telomere length using monochrome multiplex qPCR. Annual, weekly and daily exposures to nitrogen oxides and particulate matter were obtained from urban dispersion models (2008–10) and tobacco smoke by urinary cotinine. Ethnicity was assessed by self-report and continental ancestry by analysis of 28 random genomic markers. We used linear mixed effects models to examine associations with telomere length. Results: Telomere length increased with increasing annual exposure to NOx (model coefficient 0.003, [0.001, 0.005], p < 0.001), NO2 (0.009 [0.004, 0.015], p < 0.001), PM2.5 (0.041, [0.020, 0.063], p < 0.001) and PM10 (0.096, [0.044, 0.149], p < 0.001). There was no association with environmental tobacco smoke. Telomere length was increased in children reporting black ethnicity (22% [95% CI 10%, 36%], p < 0.001) Conclusions: Pollution exposure is associated with longer telomeres in children and genetic ancestry is an important determinant of telomere length. Further studies should investigate both short and long-term associations between pollutant exposure and telomeres in childhood and assess underlying mechanisms. Highlights: This is the first study on air pollution and telomere length in children. Genetic ancestry is a major determinant of telomere length in children. Continuous exposure to pollution is associated with telomere elongation. Future research should investigate longitudinal effects on telomeres.